Calcium Oscillations and its Functional Siognificance in Chronobiology of Pancreatic Î²-Cells: The Art of Discovering Science - Ahmed, Meftun; Fariduddin, KM; Khanam, Fatima; Begum, Jesmin Ara; Ara, Zinat; Deb, Samarjit (Ibrahim Medical College Journal, 2009)
doi: 10.3329/imcj.v1i1.2891 Ibrahim Med. Coll. J. 2007; 1(1): 21-31